2021
DOI: 10.3389/fimmu.2021.789145
|View full text |Cite
|
Sign up to set email alerts
|

Is It Possible to Intervene in the Capacity of Trypanosoma cruzi to Elicit and Evade the Complement System?

Abstract: Chagas’ disease is a zoonotic parasitic ailment now affecting more than 6 million people, mainly in Latin America. Its agent, the protozoan Trypanosoma cruzi, is primarily transmitted by endemic hematophagous triatomine insects. Transplacental transmission is also important and a main source for the emerging global expansion of this disease. In the host, the parasite undergoes intra (amastigotes) and extracellular infective (trypomastigotes) stages, both eliciting complex immune responses that, in about 70% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 114 publications
(126 reference statements)
0
5
0
Order By: Relevance
“…Vaccinated animals show a potent antibody response, with higher titers than those previously obtained in immunizations with rTcTASV-C adjuvanted with aluminum hydroxide, saponin, and/or U-Omp19 ( Caeiro et al., 2018 , 2020 ). In addition, functional antibodies triggered by vaccination contribute to the complement-mediated lysis of trypomastigotes, which is a desirable immune mechanism that interferes with the initial phase of infection ( Lidani et al., 2019 ; Ramírez-Toloza et al., 2021 ). The improvement in humoral response may be due to the already reported adjuvant capacity of the baculovirus ( Abe and Matsuura, 2010 ; Molina et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vaccinated animals show a potent antibody response, with higher titers than those previously obtained in immunizations with rTcTASV-C adjuvanted with aluminum hydroxide, saponin, and/or U-Omp19 ( Caeiro et al., 2018 , 2020 ). In addition, functional antibodies triggered by vaccination contribute to the complement-mediated lysis of trypomastigotes, which is a desirable immune mechanism that interferes with the initial phase of infection ( Lidani et al., 2019 ; Ramírez-Toloza et al., 2021 ). The improvement in humoral response may be due to the already reported adjuvant capacity of the baculovirus ( Abe and Matsuura, 2010 ; Molina et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Trypanosoma cruzi has on its surface a wide range of molecules that interfere both in the initiation of the complement system pathways and in the assembly of C3 convertase. Among the important molecules for resistance to attack by the complement system are calreticulin TcCRT [46], TcCRP [47], TcCRIT [48], GP58/68 [49], and T-DAF [50], which are differentially expressed at different stages and by different strains of the parasite [51]. Furthermore, the induction of the release of extracellular vesicles (EVs) by T. cruzi also participates in the inhibition of the complement system.…”
Section: The Host Immune Response Against T Cruzi Is Effective But No...mentioning
confidence: 99%
“… 45 More recently, work by Arturo Ferreira and his team have demonstrated that other parasites, particularly Tryanosoma cruzi , also present CRT on their cell surface to evade attack by the complement system. 46 This early work provoked an interest to study CRT—immune interactions further but did not explain how CRT cell surface expression was regulated either in humans or more primitive species.…”
Section: Extracellular Calreticulinmentioning
confidence: 99%